2016
DOI: 10.1248/bpb.b16-00248
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <i>Yokukansan</i>, a Traditional Herbal Preparation Used for the Behavioral and Psychological Symptoms of Dementia, on the Drug–Metabolizing Enzyme Activities in Healthy Male Volunteers

Abstract: The concomitant use of herb and prescription medications is increasing globally. Herb-drug interactions are therefore a clinically important problem. Yokukansan (YKS), a Japanese traditional herbal medicine, is one of the most frequently used herbal medicines. It is effective for treating the behavioral and psychological symptoms of dementia. We investigated the potential effects of YKS on drug-metabolizing enzyme activities in humans. An open-label repeat-dose study was conducted in 26 healthy Japanese male v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Furthermore, it has been reported that the inhibitory potential of YKS and RKT against P-gp was low in an ATPase assay [ 28 ] and did not affect the plasma pharmacokinetics of digoxin in mice [ 19 ]. Ito et al [ 19 ] and Soraoka et al [ 29 ] also evaluated the effects of several Kampo medicines on CYP3A, which is known to have considerable overlap in substrate specificity and tissue localization of P-gp [ 30 ], and it has been reported that the inhibition rate of YKS on metabolic activity was low in mice and humans. Combining the above results, the P-gp inhibitory effect appears to be low in all five Kampo medicines examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that the inhibitory potential of YKS and RKT against P-gp was low in an ATPase assay [ 28 ] and did not affect the plasma pharmacokinetics of digoxin in mice [ 19 ]. Ito et al [ 19 ] and Soraoka et al [ 29 ] also evaluated the effects of several Kampo medicines on CYP3A, which is known to have considerable overlap in substrate specificity and tissue localization of P-gp [ 30 ], and it has been reported that the inhibition rate of YKS on metabolic activity was low in mice and humans. Combining the above results, the P-gp inhibitory effect appears to be low in all five Kampo medicines examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this result, MEM has been demonstrated to be hardly metabolized by human CYP in studies using recombinant CYP isoforms; however, a part of it was metabolized to the gludantan form (furanose type glucuronic acid conjugate), 6-hydroxy form, and 4-hydroxy form [1]. YKS did not affect the induction and inhibition of CYPs and non-CYP enzymes [31,33,34,35]. Combined with these findings, the present results infer that plasma and brain concentrations of MEM may not be affected by co-treatment with YKS, although more detailed studies are necessary in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cytochrome P450 (CYP) 3A4 was shown mainly to contribute to GM metabolism in human liver microsomes [30]. In a clinical study, seven-day continuous administration of YKS did not affect the activity of CYP1A2, CYP2D6, CYP3A, xanthine oxidase, or N -acetyltransferase 2 [31]. GM was also reported to be excreted in the urine [32]; however, it is not known whether the ingredients of YKS, including GM, are substrates of their transporters, and whether they induce or inhibit the transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Age appears to be another influence factor of pharmacokinetics, for the age-related differences in gastric emptying rate, the concentration of serum proteins, and the activity levels of drug-metabolizing enzymes, as well as the function of liver and kidney [122, 123]. Specifically, children exhibit increased CL of certain drugs, while elders show the opposite trend.…”
Section: Influence Of Other Factorsmentioning
confidence: 99%